2017
DOI: 10.15406/jhvrv.2017.05.00163
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Herpes Simplex Virus Type 1 and 2 among Women Attending Antenatal and Gynecology Clinics in Sana'a City-Yemen

Abstract: Herpes simplex virus (HSV) infection is one of the worldwide infections. HSV-1 causes herpes labial and HSV-2 is the main cause of genital ulcer. Host's immune response to HSV defines by the presence of neutralizing antibodies to HSV in serum of newly and previously infected persons. A cross-sectional study was designed to determine the prevalence of HSV antibodies and potential risk factors of HSV infections among women attending some hospitals and health centers in Sana'a city based on type-specific serologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, the highest seropositive was 100% (11/11, 3/3) and among age groups 46-55 and (3/3) 56-65 years old. Other study in Yemen, showed highest seroprevalence for HSV1 among women was 100 % 108/108) in age 14-24 years old, > 46 years old (33). In comparison, the lowest seroprevalence was 98.28 (25/28) in age group 26-35 years old.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In this study, the highest seropositive was 100% (11/11, 3/3) and among age groups 46-55 and (3/3) 56-65 years old. Other study in Yemen, showed highest seroprevalence for HSV1 among women was 100 % 108/108) in age 14-24 years old, > 46 years old (33). In comparison, the lowest seroprevalence was 98.28 (25/28) in age group 26-35 years old.…”
Section: Discussionmentioning
confidence: 82%
“…(313/315) (33). Neighbor country, KSA population had seroprevalence of HSV1 was 90% and decreased to 88.7% ( 4425 /4985) ( 66 , 67 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017) in Yemen (p-value 0.6, 0.4) and Oluwapelumi et al (2020). 28,29 Another study by Mezher et al (2018) indicated that the detection of HSV-2 in women who had a history of abortion was higher than in pregnant, and that may improve the probability of this virus as one of the main viral agents that cause abortion. Many studies have suggested that HSV-2 infection may be a risk factor for miscarriage abortion; nevertheless, HSV-2 infection was detected in a small percentage of women with a history of abortion, suggesting that HSV infection is unlikely to be a major factor in abortion.…”
Section: Discussionmentioning
confidence: 99%